High definition for systems biology of microbial communities: metagenomics gets genome-centric and strain-resolved. (June 2016) - Turaev, Dmitrij; Rattei, Thomas
Graphical abstract: Highlights: High-resolution amplicon sequencing allows taxonomic profiling on strain level. Multiple-coverage binning methods enable genome-centric metagenomics. Novel methods facilitate genome reconstruction of closely related strains. Predictive modeling of microbiota promoted by high-resolution input data. New tools are needed for the interpretation of genomes from metagenomes. Abstract : The systems biology of microbial communities, organismal communities inhabiting all ecological niches on earth, has in recent years been strongly facilitated by the rapid development of experimental, sequencing and data analysis methods. Novel experimental approaches and binning methods in metagenomics render the semi-automatic reconstructions of near-complete genomes of uncultivable bacteria possible, while advances in high-resolution amplicon analysis allow for efficient and less biased taxonomic community characterization. This will also facilitate predictive modeling approaches, hitherto limited by the low resolution of metagenomic data. In this review, we pinpoint the most promising current developments in metagenomics. They facilitate microbial systems biology towards a systemic understanding of mechanisms in microbial communities with scopes of application in many areas of our daily life.